Implementasi Kegiatan Posyandu sebagai Upaya Preventif dan Promotif Kesehatan untuk Bayi dan Lansia - Erna Fitriatun; Sukarman Sukarman; Indri Susilawati; Muhammad Satria Mulyajaya; Sri Erny Muliyani; Muhsan Muhsan (Insan Kreasi Media, 2026)
This community service program aimed to implement Posyandu (Integrated Health Service Post) activities as a preventive and promotive strategy to improve the health status of infants and older adults. The program was initiated in response to the need for accessible primary healthcare services, particularly for vulnerable populations such as infants and the elderly. Infants require regular growth and developmental monitoring to facilitate the early detection of health problems, while older adults benefit from routine health assessments to identify risk factors for non-communicable diseases and maintain their overall quality of life. The program employed a participatory and educational approach that emphasized community involvement in preventive and health-promoting activities. The target participants included infants, their parents or caregivers, and older adults. The implementation consisted of four stages: preparation, implementation, evaluation, and follow-up. Activities for infants included weight and height measurements, documentation of health records in child health monitoring books, and health education on exclusive breastfeeding, balanced nutrition, immunization, and growth and developmental monitoring. For older adults, activities included blood pressure screening, health interviews to identify current health concerns, documentation of examination results, and health education on healthy lifestyles, light physical activity, and the prevention of degenerative diseases. The findings indicate that the implementation of Posyandu served as an effective platform for the early detection of health conditions, enhanced community knowledge, and strengthened community participation in maintaining the health of infants and older adults. Participants demonstrated high levels of engagement throughout the program and gained a better understanding of the importance of routine health examinations, continuous monitoring of child growth and development, and the adoption of healthy lifestyle practices during older adulthood.